Leukonychia is the most common nail change in Alopecia areata patients: A retrospective study in 207 patients - Aktas, Habibullah; Unal, Mehmet (Annals of Medical Research, 2021)
None
Keywords: Alopecie Areata; Nail Changes; Leukonychia.